Experimental Investigation of Environment Temperature Effect on Fatigue of Shape Memory Alloy with Phase Transformation (Eurasian Journal of Engineering and Technology, 2023)
When compared to other materials used in engineering applications, shape-memory alloys (SMAs) are a type of smart material have superior mechanical properties, distinguished by their capacity to return their original shape when heated. At low temperatures, they have low yield strength, facilitating their transformation into any form. The alloy maintains this form until the temperature rises higher than the temperature of their transformation, then return to its original shape